The Endocannabinoid System and Cannabidiol: Past, Present, and Prospective for Cardiovascular Diseases - Martina Rabino; Sara Mallia; Elisa Castiglioni; Davide Rovina; Giulio Pompilio; Aoife Gowran (MDPI AG, 2021)
In the past, cannabis was commonly associated with mysticism and illegality. Fortunately, in recent years perspectives and discourses have changed. More prominence has been given to the rigorous scientific effort that led to the discovery of cannabis' many physiological actions and endogenous signalling mechanisms. The endocannabinoid system is a complex and heterogeneous pro-homeostatic network comprising different receptors with several endogenous ligands, numerous metabolic enzymes and regulatory proteins. Therefore, it is not surprising that alterations and dysfunctions of the endocannabinoid system are observed in almost every category of disease. Such high degree of pathophysiological involvement suggests the endocannabinoid system is a promising therapeutic target and prompted the translation of resurgent scientific findings into clinical therapies. Shifting attitudes toward cannabis also raised other matters such as increased patient awareness, prescription requests, self-medication, recreational use, recognition of new knowledge gaps, renewed scientific activity, and seemingly exponential growth of the cannabis industry. This review, following a general overview of cannabis and the endocannabinoid system, assiduously describes its role within the context of cardiovascular diseases, paying particular attention to the Janus influence that endocannabinoid system modulators can have on the cardiovascular system.